2017
DOI: 10.4236/jacen.2017.61002
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Arsenic Toxicity in the Soil-Plant System by Using Zinc Fertilizers

Abstract: Availability of soil arsenic (As) and plant As at various levels of zinc (Zn) and As applications were examined. A pot-culture experiment with a leafy vegetable, Kalmi (Ipomoea aquatica), on an Inceptisols, was conducted where As was applied with irrigation water at the rates of 0 mg/L (As control), 0.5 mg/L, 1 mg/L and 2 mg/L and Zn was added to the soil as ZnCl 2 solution at the rate of 0 mg/L (Zn control), 1 mg/L, 2 mg/L and 3 mg/L during pot preparation. The experiment was conducted in triplicates for 45 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The reduction of the soil solution As concentrations upon the Zn addition has been previously reported and is commonly attributed to the co-sorption or precipitation process involving Zn and As [15,16,19,20]. The Zn concentrations in the solution of single spiked soils reach >1mM and the same is true for AsO 4 −3 concentrations.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The reduction of the soil solution As concentrations upon the Zn addition has been previously reported and is commonly attributed to the co-sorption or precipitation process involving Zn and As [15,16,19,20]. The Zn concentrations in the solution of single spiked soils reach >1mM and the same is true for AsO 4 −3 concentrations.…”
Section: Discussionmentioning
confidence: 58%
“…In well aerated soils, As is present as As(V), that is, different anions of AsO 4 (e.g., H 2 AsO 4 − ) with a strong sorption on Fe-Al oxyhydroxides, and with phosphate (PO 4 ) anions or organic matter as competing compounds [14]. Increasing the soil Zn decreases the As solubility in soil [15,16], whereas increasing the AsO 4 decreases the Zn solubility, and has also been shown in studies using Fe-oxides as adsorbents [17,18]. This may occur because of the precipitation of zinc arsenate or because of the formation of ternary Zn-As-(hydro)oxides complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Although Pi supply suppressed the As uptake by plants in the hydroponics, high S addition increased As uptake and decreased Pi content influencing the As-Pi interaction in plants. Application of As and Zn to soils shows an antagonistic relationship such as Zn in soils (at application rate of 3 mg/L) reduced As availability in soils and uptake in plants (Sanchary and Huq, 2017). Arsenic accumulation by plants is controlled by the oxidation state, As and P forms and plant species.…”
Section: Mechanisms Of As Toxicity To Plantsmentioning
confidence: 99%
“…The difference between interaction patterns may result from the selected model species and dose metrics. To date, not many phytotoxicity studies on metal(loid) mixtures are available in soil systems, and most of them are analyzed on the basis of total soil concentrations (Das et al, 2016;Kader et al, 2017;Sanchary and Huq, 2017). For example, the study of Cao et al (2007) observed antagonistic interactions between As and Cd on root elongation of wheat (Triticum aestivum L.) based on total metal concentrations in soil.…”
Section: Introductionmentioning
confidence: 99%